Translational biomaterials — the journey from the bench to the market — think 'product'. (August 2016) - Serban, Monica Andrea
Graphical abstract: Highlights: Translational challenges impact the growth rate of commercially available biomaterial-based therapies. The understanding of the pertinent regulatory challenges is key in successful biomaterial translation. A pragmatic product development approach might enhance translational success. Abstract : Biomaterial research has been gaining popularity over the past decades and, in parallel, the number of biomaterial-based therapies has been increasing. There is still however, a disconnection between the number of developed biomaterials and those that make it to the market. In this context, a review of the biomaterial development trends in both industry and academia, specifically of biomaterials that were successfully translated from bench side to the clinic and the market, is warranted.